Pendampingan Industri Perumahan Lumpia Sebagai Oleh-Oleh Khas Semarang - Imron Widjaja; Tan Winda; Iswahyudi Iswahyudi (SERVIRE: Jurnal Pengabdian Kepada Masyarakat, 2023)
The food souvenir industry in Semarang is currently dominated by several well-known celebrity brands. This large capital business hampers the competitiveness of the local souvenir home food industry. This community partnership program works with home industry partners "Yudi Lumpia" to gain their competitiveness. The problems experienced by partners are: (1) production is not efficient, (2) packaging is not up to standard, (3) business management, finance and marketing are not good, and (4) do not have PIRT and Halal permits. To overcome these problems assistance has been carried out, including: (1) procurement of production equipment that has been upgraded to overcome production inefficiencies; (2) repackaging the product using a sealer and redesigning the packaging box; (3) mentoring and workshops on market research topics, product diversification, financial management, stock management, and e-commerce; and (4) assistance in obtaining PIRT and Halal permits. After the mentoring efforts, the following results were obtained: (1) increased production efficiency and safety; (2) better product shelf life; (3) increasing understanding and changing behavior related to business management, finance, and marketing; (4) expansion of marketing and (5) issuance of PIRT licenses. Industri oleh-oleh makanan di Semarang saat ini didominasi oleh beberapa merek selebriti ternama. Bisnis modal besar ini menghambat daya saing industri makanan rumahan oleh-oleh lokal. Program kemitraan masyarakat ini bekerja sama dengan mitra industri rumah tangga “Yudi Lumpia” untuk mendapatkan daya saing mereka. Permasalahan yang dialami mitra adalah: (1) produksi tidak efisien, (2) pengemasan tidak sesuai standar, (3) pengelolaan usaha, keuangan, dan pemasaran kurang baik, dan (4) tidak memiliki PIRT dan izin Halal . Untuk mengatasi permasalahan tersebut telah dilakukan pendampingan antara lain: (1) pengadaan alat produksi yang telah diupgrade untuk mengatasi inefisiensi produksi; (2) pengemasan ulang produk menggunakan sealer dan desain ulang kotak kemasan; (3) pendampingan dan workshop dengan topik riset pasar, diversifikasi produk, manajemen keuangan, manajemen stok, dan e-commerce; dan (4) pendampingan untuk memperoleh PIRT dan izin Halal. Setelah upaya pendampingan diperoleh hasil: (1) peningkatan efisiensi dan keamanan produksi; (2) umur simpan produk yang lebih baik; (3) peningkatan pemahaman dan perubahan perilaku terkait manajemen usaha, keuangan, dan pemasaran; (4) perluasan pemasaran dan (5) penerbitan izin PIRT.